Joint effect of 25-hydroxyvitamin D and secondhand smoke exposure on hypertension in non-smoking women of childbearing age: NHANES 2007-2014 - Qianqian Shen; Qian Xu; Guoju Li; Lisheng Ren; Zhenhong Zhang; Yangting Zhang; Zhaoyi Zhong; Xiaona Li; Qiuzhen Wang (BMC, 2021)
Abstract Background Vitamin D deficiency (VDD) may increase the risk of hypertension in women of childbearing age, who may be exposed to secondhand smoke (SHS) simultaneously. Till now, few studies have investigated the joint effects of VDD and SHS on hypertension in this population. We evaluated whether exposure to SHS modified the association between VDD and hypertension. Methods Data from National Health and Nutrition Examination Surveys (NHANES) 2007-2014 were analyzed. Our research subjects were 2826 nonsmoking and nonpregnant women of childbearing age (20-44 years old). Hypertension was defined based either on systolic blood pressure (SBP) ≥ 130 mmHg and/or diastolic blood pressure (DBP) ≥ 80 mmHg or on now taking prescribed medicine for hypertension. The directed acyclic graphs (DAG) and the back-door criterion were used to select a minimal sufficient adjustment set of variables (MSAs) that would identify the unconfounded effect of 25(OH)D and hypertension. The interactive effect of VDD and SHS on hypertension was evaluated by using logistic regression models, followed by strata-specific analyses. Results The prevalence of VDD in the hypertension group was significantly higher than that in the non-hypertension group (48.2% vs 41.0%, P = 0.008), as well as the exposure rate of SHS (39.1% vs 33.8%, P = 0.017). VDD was independently associated with nearly 50% increased risk of hypertension [adjusted odds ratio (aOR) = 1.43, 95% confidence interval (CI): 1.01, 2.04], while no significant association was observed between SHS and hypertension. However, SHS showed a significant synergistic effect on VDD with a higher aOR of 1.79 (95% CI: 1.14, 2.80) (P interaction  = 0.011). This synergistic effect was more obvious when stratified by BMI (in overweight women, aOR, 95% CI =4.74, 1.65-13.60 for interaction vs 2.33, 1.01-5.38 for VDD only) and race (in Non-Hispanic Black women, aOR, 95% CI =5.11, 1.58-16.54 for interaction vs 2.69, 1.10-6.62 for VDD only). Conclusion There exist synergistic effects of SHS and VDD on the prevalence of hypertension in American women of childbearing age, with more significant effects in women who were overweight or Non-Hispanic Black. Further studies are warranted to verify this finding in other populations, and the molecular mechanisms underlying the joint effect of SHS and VDD need to be elucidated.